Effects of activated charcoal on rooting of in vitro apple (Malus domestics Borkh.) shoots - Magyar-Tábori, K.; Dobránszky, J.; Jámbor-Benczúr, E.; Lazányi, J.; Szalai, J. (International Journal of Horticultural Science, 2001)
Rooting of in vitro 'Royal Gala' shoots was studied under different conditions of root induction and root elongation phase. The rooting capacity was affected by both rooting phases. Very high rooting percentage could be reached with both liquid and solid root induction media. Raising the temperature from 22 °C to 26 °C during root induction phase increased the rooting percentage. Presence of activated charcoal in root elongation media can affect the number of roots per rooted shoots and can increase the rooting percentage, the length of roots and the rate of survival depending also on other conditions during rooting. Presence of NAA in root elongation media reduced the number and the length of roots considerably. Favourable effect of activated charcoal on rooting was mainly due to adsorption of NAA.